Chemical Modification and Characterization of Yeast Cells for Extraction of Metal Ion in Water Sample - Ahmad Panahi, Homayon (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A novel biosorbent is prepared by coupling a cibacron blue to yeast cells. The chemically modified yeast cells with mentioned ligand has been characterized by Fourier transform infrared spectroscopy and elemental analysis and applied for the preconcentration and extraction of trace Ni(II) from water samples. The optimum pH value for sorption of the nickel ions was 8. The sorption capacity of yeast cells- cibacron blue is 12.2 mg. gâˆ’1. A recovery of 91.4% was obtained for Ni(II) when eluted with 0.5 M HCl/HNO3 (3:1). The equilibrium data of Ni(II) adsorption on yeast cells- cibacron blue was analyzed using Langmuir model. The method was applied for Ni(II) determination in sea water sample.